To compare the efficacy of drotaverine hydrochloride with hyoscine butylbroumide for increasing the rate of cervical dilatation - Kausar, Uzma; Siddiqui, Nikhat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In order to accelerate the labour apart from early amniotomy and early administration of oxytocin, the use of antispasmodic agents like drotaverine and hyoscine butylbromide to hasten the first stage of labor is a common practice. Considering the promising results of hyoscine butylbromide, the present study was planned to to compare the efficacy of drotaverine hydrochloride with hyoscine butylbroumide for increasing the rate of cervical dilatation. Methods: This prospective placebo-controlled crossover study was carried out at Department of Obstetrics and Gynaecology, Era’s Lucknow Medical College, Lucknow. The study was conducted on 60 women in labour who were randomly allocated to group I, group II and group III of 20 patients each. In group I, no intervention was done and comprised the control group. The women in group II were injected intramuscularly one ampoule (20mg) of hyoscine butylbromide. The women in Group III were injected Inj. Drotavrine one ampoule (40mg) intramuscularly at 3 cm dilatation. The data collected was analysed using SPSS Version 15.0. Suitable statistical tests were applied. Results: Majority of subjects were aged between 21-30 years, were multipara and had spontaneous labour. Mean duration of first stage of labour ranged from 3 hoour 34 minutes (drotaverine hydrochloride) to 5 hour 45 minutes (control group) showing a significant intergroup difference. Mean total duration of labour ranged from 4 hr 11 minutes (drotaverine hydrochloride and hyoscine butylbromide groups) to 6 hr 26 minutes (control group) showing a significant intergroup difference (p <0.001). Majority of deliveries were full term normal deliveries. Conclusions: Both drotaverine hydrochloride and hyoscine butylbromide could effectively reduce first stage as well as total duration of labour. Further studies are recommended to establish the comparative efficacy in terms of a side effect profile and relatively efficacy in view of various clinico-demographic variables.